INNER CONFLICT AS THE EFFECT OF BODY SHAMING IN THE FILM TALL GIRL (2019) BY SAM WOLFSON - Teahni, Lantik Wahyu; Wahyuni (Faculty of Letters Universitas Balikpapan, 2025)
This research focuses on inner conflict as an effect of body shaming in the film Tall Girl 2019. There are two objectives of this research, namely; to identify the types of body shaming present in the film Tall Girl 2019 by Sam Wolfson and to describe the impact of body shaming on inner conflict in the film Tall Girl 2019 by Sam Wolfson. The theory used in this research is the analysis of psychology of literature approach using Dolezal's body shaming theory and Kurt Lewin's inner conflict theory. The methodology used is qualitative research where the researcher presents the problem descriptively. The results show two types of body shaming experienced by Jodi, namely Acute Body Shame and Chronic Body Shame. When body shaming affects inner conflict, there are influences of inner conflict found in this study, namely approaching, avoiding, and approaching-avoiding.